2010
DOI: 10.4103/0972-124x.65436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retraction materials on gingival health: A histopathological study

Abstract: Background:Gingival retraction methods are used in dentistry for impressions of subgingival crown margins, such as, mechanical, chemical, chemicomechanical, and surgical. These methods may injure the gingival sulcular epithelium. Hence, the present study is carried out to evaluate the effect of different retraction materials, such as, Expasyl, Magic Foam Cord, and impregnated retraction cord on the gingival sulcular epithelium.Materials and Methods:This study included 30 cases of bilateral premolar extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 7 publications
2
57
0
2
Order By: Relevance
“…5 Phatale et al (2010) showed a higher percentage of intact junctional epithelium histologically with Expasyl  in comparison to the use of a retraction cord. 6 Junctional epithelium that surrounds implants is at greater risk of experiencing penetration damage than the more robust sulcus of natural teeth, when exposed to trauma such as gingival cord retraction procedures. Placement of a cordless retraction paste eliminates the risk of laceration of the sulcular groove.…”
Section: Discussionmentioning
confidence: 99%
“…5 Phatale et al (2010) showed a higher percentage of intact junctional epithelium histologically with Expasyl  in comparison to the use of a retraction cord. 6 Junctional epithelium that surrounds implants is at greater risk of experiencing penetration damage than the more robust sulcus of natural teeth, when exposed to trauma such as gingival cord retraction procedures. Placement of a cordless retraction paste eliminates the risk of laceration of the sulcular groove.…”
Section: Discussionmentioning
confidence: 99%
“…The gingival displacement process generally promotes changes in the microcirculation of periodontal tissues, causing inflammation and an increase in the amount of crevicular fluid production 16 . Phatale et al 17 observed that junctional epithelium of teeth after gingival displacement with Ultrapak cord 00 impregnated with 5% AlCl 3 underwent major changes, such as intracellular degeneration and desquamation due to the chemical displacement methods used 17 . Therefore, the technique with gingival displacement cord, either associated with a chemical agent, or not, may damage the periodontal tissue and increase the amount of crevicular fluid [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Phatale et al 17 observed that junctional epithelium of teeth after gingival displacement with Ultrapak cord 00 impregnated with 5% AlCl 3 underwent major changes, such as intracellular degeneration and desquamation due to the chemical displacement methods used 17 . Therefore, the technique with gingival displacement cord, either associated with a chemical agent, or not, may damage the periodontal tissue and increase the amount of crevicular fluid [16][17][18] . Therefore, a sensitive technique associated with correct manipulation of the soft tissues 17 during the introduction of the gingival displacement cord can be a very important and effective factor to avoid exacerbated tissue irritations 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Histological studies have proved that it does not cause any adverse effects on the gingival and periodontal tissues and exhibits excellent biocompatibility. 9 Hemostatic agents ensure an easy and efficient way of bonding orthodontic attachments to impacted teeth immediately after surgical exposure and will go a long way in helping orthodontists bond better in a bloody field, minimizing the risk of bond failure. The bonded attachments can be immediately subjected to orthodontic forces without any risk of premature failure of the bond.…”
Section: Discussionmentioning
confidence: 99%